Coercion and Wage Labour Exploring work relations through history and art - Batista, Anamarija; Müller, Viola Franziska; Peres, Corinna (Work Around the World, 2023)
Coercion and Wage Labour presents novel histories of people who experienced physical, social, political or cultural compulsion in the course of paid work. Broad in scope, the chapters examine diverse areas of work including textile production, war industries, civil service and domestic labour, in contexts from the Middle Ages to the present day. They demonstrate that wages have consistently shaped working people's experiences, and failed to protect workers from coercion. Instead, wages emerge as versatile tools to bind, control, and exploit workers. Remuneration mirrors the distribution of power in labour relations, often separating employers physically and emotionally from their employees, and disguising coercion. The book makes historical narratives accessible for interdisciplinary audiences. Most chapters are preceded by illustrations by artists invited to visually conceptualise the book's key messages and to emphasise the presence of the body and landscape in the realm of work. In turn, the chapter texts reflect back on the artworks, creating an intense intermedial dialogue that offers mutually relational 'translations' and narrations of labour coercion. Other contributions written by art scholars discuss how coercion in remunerated labour is constructed and reflected in artistic practice. The collection serves as an innovative and creative tool for teaching, and raises awareness that narrating history is always contingent on the medium chosen and its inherent constraints and possibilities. Praise for Coercion and Wage Labour This is a pioneering volume. It makes a well-founded break with the widespread misconception that wage labour is by definition free from coercion. The 14 historical case studies cover a vast geographical area and review a long time period. Together, they lead to the conclusion that wage labourers too were subject to many forms of coercion and that usually their "freedom" was and is only relative. But something else makes this book special: throughout the text there are artistic illustrations that enter into a dialogue with the individual chapters and create an inspiring interaction that complements the volume's interdisciplinary nature.' Marcel van der Linden, International Institute of Social History, Amsterdam